Immunomodulatory activity of β-glucan-containing exopolysaccharides from Auricularia auricular in phagocytes and mice infected with Cryptococcus neoformans. (16th May 2019) - Basso, A M M; De Castro, R J A; de Castro, T B; Guimarães, H I; Polez, V L P; Carbonero, E R; Pomin, V H; Hoffmann, C; Grossi-de-Sa, M F; Tavares, A H; Bocca, A L
Abstract: Current antifungal drugs present poor effectiveness and there is no available vaccine for fungal infections. Thus, novel strategies to treat or prevent invasive mycosis, such as cryptococcosis, are highly desirable. One strategy is the use of immunomodulators of polysaccharide nature isolated from mushrooms. The purpose of the present work was to evaluate the immunostimulatory activity of β-(1, 3)-glucan-containing exopolysaccharides (EPS) from the edible mushrooms Auricularia auricula in phagocytes and mice infected with Cryptococcus neoformans . EPS triggered macrophages and dendritic cell activation upon binding to Dectin-1, a pattern recognition receptor of the C-type lectin receptor family. Engagement of Dectin-1 culminated in pro-inflammatory cytokine production and cell maturation via its canonical Syk-dependent pathway signaling. Furthermore, upon EPS treatment, M2-like phenotype macrophages, known to support intracellular survival and replication of C. neoformans, repolarize to M1 macrophage pattern associated with enhanced production of the microbicidal molecule nitric oxide that results in efficient killing of C. neoformans . Treatment with EPS also upregulated transcript levels of genes encoding products associated with host protection against C. neoformans and Dectin-1 mediated signaling in macrophages. Finally, orally administrated β-glucan-containing EPS from A. auricular enhanced the survival of mice infected with C. neoformans . In conclusion, the results demonstrate that EPS from A. auricula exert immunostimulatory activity in phagocytes and induce host protection against C. neoformans, suggesting that polysaccharides from this mushroom may be promising as an adjuvant for vaccines or antifungal therapy.